Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/s16030413
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Hyperspectral or Trichromatic Measurements of Ocean Color Data into Spectral Classes

Abstract: We propose a method for classifying radiometric oceanic color data measured by hyperspectral satellite sensors into known spectral classes, irrespective of the downwelling irradiance of the particular day, i.e., the illumination conditions. The focus is not on retrieving the inherent optical properties but to classify the pixels according to the known spectral classes of the reflectances from the ocean. The method compensates for the unknown downwelling irradiance by white balancing the radiometric data at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…HSI has been widely used in environmental monitoring [1], mineral exploration [2], agricultural remote sensing [3], vegetation ecology [4], ocean remote sensing [5], and other earth observation tasks. In these applications, because HSI exhibits mixed land cover categories, resulting in high intraclass variability and interclass similarity, it is a huge challenge for any classification model.…”
Section: Introductionmentioning
confidence: 99%
“…HSI has been widely used in environmental monitoring [1], mineral exploration [2], agricultural remote sensing [3], vegetation ecology [4], ocean remote sensing [5], and other earth observation tasks. In these applications, because HSI exhibits mixed land cover categories, resulting in high intraclass variability and interclass similarity, it is a huge challenge for any classification model.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of other classifications have been developed and used for various applications. Representative schemes have been based on • Cluster Analysis of R rs spectra: Eleveld et al (2017); Melin and Vantrepotte (2015); Prasad and Agarwal (2016); Wei et al (2016) • Fuzzy Logic Classification of R rs spectra: Moore et al (2001Moore et al ( , 2009Moore et al ( , 2014 • CHAPTER 5…”
Section: Other Classification Schemesmentioning
confidence: 99%
“…Remotely sensed hyperspectral data which is collected by hyperspectral sensors consist of hundreds of contiguous spectral bands with high resolutions [1,2]. Recent studies in remote sensing have shown that hyperspectral images (HSIs) have been successfully applied in precision agriculture, urban planning, environmental monitoring and various other fields [3][4][5][6]. One of the typical characteristics of an HSI is that it cannot only obtain the scene information in the two-dimensional space of the target image but can also acquire one-dimensional spectral information with a high resolution to characterize the physical property.…”
Section: Introductionmentioning
confidence: 99%